Membujur lalu suatu pengalaman orang Melayu dalam pengurusan - Mohd Ali Hj. Hashim (Utusan Publications & Distributors Sdn Bhd, 1996)
Success of PKENJ, Johor State Economic Development Corporation as a corporate organization and an Islamic business institution in Malaysia.